Money, morality and magistrates. Prosecuting and judging in the Republic of Benin. Issue 2 (4th May 2018) - Andreetta, Sophie; Kolloch, Annalena
Abstract: Since 2012, Beninese magistrates have gone on multiple strikes. Most of them complain about their substantial workload, low pay, and poor working conditions. They also highlight the discrepancies between magistrates' social status and what their families expect from them. However, judges and prosecutors also insist on the importance of their work and on the ethics that goes together with it. This paper analyses the discourses and representations of the social and professional status of Beninese judges, showing that they are contingent upon gender, political and economic contexts. It delves into the magistrate's changing relationship to the state, as well as into their professional identities and daily practices.